2017
DOI: 10.1007/s00428-017-2072-8
|View full text |Cite
|
Sign up to set email alerts
|

Histological and immunohistochemical characteristics of undifferentiated small round cell sarcomas associated with CIC-DUX4 and BCOR-CCNB3 fusion genes

Abstract: CIC-DUX4 and BCOR-CCNB3 fusion-gene-associated small round cell sarcomas account for a proportion of pediatric small round cell sarcomas, but their pathological features have not been sufficiently clarified. We reviewed a large number of soft tissue tumors registered at our institution, retrieved the cases of unclassified tumors with a small round cell component, and subjected them to histopathological, immunohistochemical, and gene profile analysis. We reviewed 164 cases of unclassified tumors with a small ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 20 publications
5
78
2
4
Order By: Relevance
“…It is less well known that even though the genomic translocation is highly specific for prostate cancer, ERG protein expression is seen in a variety of other tumors, too. This includes, apart from vascular tumors, round cell sarcomas and leukemias, the more common differential diagnosis of urothelial carcinoma and, according to the human protein atlas (), also melanoma, testicular, and gastrointestinal tumors [22,23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…It is less well known that even though the genomic translocation is highly specific for prostate cancer, ERG protein expression is seen in a variety of other tumors, too. This includes, apart from vascular tumors, round cell sarcomas and leukemias, the more common differential diagnosis of urothelial carcinoma and, according to the human protein atlas (), also melanoma, testicular, and gastrointestinal tumors [22,23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…However, heterologous cartilaginous differentiation in these neoplasms, as seen in one of the cases in our study, has not been previously reported. From an immunophenotypic standpoint, the majority of sarcomas with BCOR fusions demonstrate nuclear expression of TLE‐1, SATB2, and BCOR . Expression of these three markers, however, is not entirely specific, since they can also be seen in a proportion of clear cell sarcomas of the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of these three markers, however, is not entirely specific, since they can also be seen in a proportion of clear cell sarcomas of the kidney. In addition, synovial sarcomas are typically positive for TLE‐1 and can express BCOR in up to 50% of cases . Larger studies evaluating the prognostic features of these neoplasms have shown a relatively favorable clinical behavior when compared to CIC ‐rearranged sarcomas, with mortality and metastatic rates that somewhat mirror those of synovial sarcoma, and favorable response to Ewing sarcoma chemotherapy .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the morphologic spectrum of BCOR-CCNB3 fusion sarcomas is broad, containing round, spindled, myxoid and, in rare cases, even pleomorphic tumors, though this latter morphology may be due in part to therapy. 70–73 …”
Section: Recurrent Polycomb-member Rearrangements Characterize a Divementioning
confidence: 99%